The Managerial Competency Development for Young tourism officials in Luang Prabang, Lao PDR - LATTANASOUVANNAPHONH, Champa; OUNPHOUVONG, Stamy; YOUTHASETH, Thongvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This paper aims to identify the component of managerial competencies of the young tourism official leaders and to develop managerial competency for young tourism leaders in Luang Prabang. Action research is designed for collecting primary data with training platform. In this action research was applied the concept of facilitation skill training as a tool for training model to develop an effective training workshop for improving managerial competency of the young tourism official leaders. The managerial competency was reviewed and interviewed with the selected ten participants from the young tourism officials, the managerial competencies are interested in developing are included: Service leadership, Innovative Management, Cooperate Governance, Financial Management and Human Resource Management. However, due to our limited time of this research project, the Service Leadership Competency training was determined as a pilot training workshop to test and to develop learning approach to improve the managerial competency of selected ten representative tourism officials.